Nonlinear Response of the Surface Energy Balance to Changes in Anthropogenic Aerosols and Irrigation Over South Asia - Veronika J. Redensek; Sonali McDermid; Deepti Singh; Geeta Persad (Earth's Future)
Abstract The regional climate impacts of anthropogenic aerosol emissions and irrigation growth in South Asia have conventionally been studied separately. These forcings have overlapping influences on surface temperature and atmospheric stability, but detection and attribution simulations typically quantify the impact of individual time‐evolving climate forcings, which does not account for nonlinear interactions between forcings or their impacts, when forcings evolve in tandem. Using transient simulations in GISS ModelE 2.1‐G, we assess the summertime surface energy balance in five different sub‐regions of South Asia by comparing the linear addition of anthropogenic aerosol and land use single‐forcing historical simulations with novel dual‐forcing simulations. We find that the combination of aerosol emissions and irrigation changes between preindustrial and present‐day increases aerosol hydration and cloud cover more strongly than does the linear addition of the individual forcings. This results in a strong nonlinear decrease in downwelling shortwave radiation, which drives subsequent nonlinearities in the surface energy balance through a relative suppression of energy availability at the surface. While aerosols and irrigation are each credited with suppressing monsoon winds and delaying onset, combined simulations of both forcings suggest that surface pressure is nonlinearly reduced over the northern Indian Subcontinent. This results in a net increase in 850 mb winds from the Bay of Bengal toward northwest India and Pakistan in combined simulations, suppressing the weakening of summer monsoon winds from single forcing results. The nonlinearities identified in our study suggest that the current framework for detection and attribution may not adequately account for potential interactions between forcings.